Monitoring The Provision Of Transnational Higher Education (TNHE) Services: The Potentials For Multi-Sectoral Cooperation. - Muhamad Jantan, Muhamad Jantan; Sirat, Morshidi; Chang Da, Wan (2008)

(untitled)
Transnational higher education (TNHE) is not a new phenomenon, though its nature and the pace of its growth are unprecedented, challenging the national systems of higher education in this region. Whilst it brings about identifiable benefits, it also raises concerns amongst nations, particularly for the importing countries that are less prepared to meet these challenges.